Dampak Terpaan Media Komunikasi Pada Usaha Tani Hortikultura Di Kelurahan Rurukan I Kota Tomohon - Timothy D.R. Ginting; Rine Kaunang; Lorraine W.Th. Sondakh; Celcius Talumingan (COCOS, 2015)
ABSTRACTThe purpose of this study was to determine what type of media a lot and frequently accessed by the farmers and the relationship between communication media exposure available with the ongoing development of farming in the village Rurukan, as well as farmers' perceptions of communication media circulating in the Village Rurukan. These results indicate that horticultural farmers in villages Rurukan already regarding the use of communication media as an information for agricultural development to marketing, communications media are often used to capture the agricultural information is television, radio, and newspaper. Communications mediais most often accessed by farmers is through themedium of television, while the communication mediumfarmersarerarely accessed via the internet, it shows that thevillage farmersto better respond Rurukan through the medium of television that is easily accessible and understood by farmers/ farmer groups so as tosaid tothe televisionasthe most influentialmedium of communication and helps farmers/ farmer groups to obtain information about his farming business management. Therefore, in this study suggested farmers / farmer groups horticulture can continue to evolve with the demands of the modern era in the use of communication media, for it sought for agricultural extension workers, farmers and farmer groups are able to call on other farmers who are not familiar with the communications media and the still use traditional farming systems to use the Media Communication switch in crops, especially internet media because the information is always updated especially regarding price, as well as jointly develop horticulture farming results while utilizing media Communications for the needs of the farmer tried.